Silika Gel Termodifikasi Dimetilamin Sebagai Penyerap Anion Fosfat - Delfitri Delfitri; Budhi Oktavia; Desy Kurniawati; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2022)
Silica gel is one type of dry silica gel which is widely used as an adsorbent. Silica has the ability to absorb because it has two active site groups that can be activated, namely a silanol group and a siloxane group. This modification was carried out to increase the ability of silica to absorb ions, one of which was phosphate anion. In waters, very high levels of phosphate anion can disrupt the marine biota ecosystem because it can cause uetrophication or decreased oxygen levels that enter the waters. The modifier compound used is dimethylamine (DMA). Silica and dimethylamine can bind to several linking compounds, namely glycidopropyltrimethoxylan (gptms). The modified silica was characterized by FTIR and the absorption results were analyzed using a UV-Vis spectrophotometer. The results of the comparison of the absorption capacity of phosphate anions after modification are greater than before modification, where the absorption capacity of silica before modification is 1,2601 mg/g with an absorption percentage of 54,46% and silica after modification is 1.9686 mg/g with an absorption percentage of 1,9686 mg/g. 85,08%.Keywords — Silica gel, Modification, Dimetilamine, Phosphate Anion